2022
DOI: 10.1002/nafm.10809
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Colonization of Upstream Habitats by Oncorhynchus Mykiss Following Culvert Modification

Abstract: Habitat fragmentation threatens the persistence of fish populations, and road crossings (e.g., culverts) are particularly problematic because they are globally ubiquitous and can block access to critical habitats. Barrier removal or modifications that allow upstream access can result in expanded distributions, increased abundances, and gene flow among historically isolated populations. Actions that promote connectivity, gene flow, and the potential expression of multiple life history forms (e.g., anadromy in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…In turn, Rogers et al (2021) found that assessments of barriers using screening tools may underestimate the extent of fish movement through culverts, and they emphasized the importance of using multiple metrics to judge passability along with consideration of temporal and spatial variation in habitats. Overall, our results from the upstream reach of GR3 (one of the three tributaries that were historically fragmented) show the strongest pattern of genetic differentiation consistent with studies that have linked impassable culverts with high levels of genetic differentiation (e.g., Torterotot et al 2014; Wood et al 2018; Knoth et al 2022), and these results further substantiate the idea that the specific characteristics of the culverts play a role in shaping genetic structure.…”
Section: Discussionsupporting
confidence: 88%
“…In turn, Rogers et al (2021) found that assessments of barriers using screening tools may underestimate the extent of fish movement through culverts, and they emphasized the importance of using multiple metrics to judge passability along with consideration of temporal and spatial variation in habitats. Overall, our results from the upstream reach of GR3 (one of the three tributaries that were historically fragmented) show the strongest pattern of genetic differentiation consistent with studies that have linked impassable culverts with high levels of genetic differentiation (e.g., Torterotot et al 2014; Wood et al 2018; Knoth et al 2022), and these results further substantiate the idea that the specific characteristics of the culverts play a role in shaping genetic structure.…”
Section: Discussionsupporting
confidence: 88%
“…However, this pattern did not hold true for control/impact research designs, and may be to the result of inherent differences between sites that confound results in such control/impact comparisons (Christie et al., 2019; Michener, 1997). Richness and density increases can be ecological indicators resulting from improved connectivity which allowed fishes to expand their distributions, access habitats to facilitate a suite of life‐history stages, and promote gene flow to recover genetic diversity (Knoth et al., 2022). However, the identity and composition of species was an important consideration that was not necessarily captured by summary metrics such as species richness.…”
Section: Discussionmentioning
confidence: 99%
“…Richness and density increases can be ecological indicators resulting from improved connectivity which allowed fishes to expand their distributions, access habitats to facilitate a suite of life-history stages, and promote gene flow to recover genetic diversity (Knoth et al, 2022). However, the identity and composition of species was an important consideration that was not necessarily captured by summary metrics such as species richness.…”
Section: In-stream Connectivitymentioning
confidence: 99%
“…In addition, reproduction occurring between anadromous and resident O. mykiss within these tributary systems may buffer population size FINE-SCALE STEELHEAD POPULATION GENETIC STRUCTURE estimates during depressed anadromous runs (Arden and Kapuscinski 2003). Genetic interactions between resident and anadromous O. mykiss have been documented in a variety of studies (Courter et al 2013), including work conducted in the Potlatch River drainage, a tributary to the lower Clearwater River (Bowersox et al 2016;Knoth et al 2022). Finally, low N e estimates in some of our study streams could be associated with smaller or marginal habitat tributaries, where mixing of wild and hatchery steelhead across tributaries may provide a mechanism for retention of high genetic diversity in the presence of low numbers of breeders (Heath et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…2016; Knoth et al. 2022). Finally, low N e estimates in some of our study streams could be associated with smaller or marginal habitat tributaries, where mixing of wild and hatchery steelhead across tributaries may provide a mechanism for retention of high genetic diversity in the presence of low numbers of breeders (Heath et al.…”
Section: Discussionmentioning
confidence: 99%